Trypanosoma brucei rhodesiense Inhibitor of Cysteine Peptidase (ICP) Is Required for Virulence in Mice and to Attenuate the Inflammatory Response - Costa, Tatiana F. R. (2023)
Universidade Federal do Rio de Janeiro. Instituto de Biofisica Carlos Chagas Filho. Rio de Janeiro, RJ, Brasil.